2012
DOI: 10.1371/journal.pone.0043521
|View full text |Cite
|
Sign up to set email alerts
|

Novel Processed Form of Syndecan-1 Shed from SCC-9 Cells Plays a Role in Cell Migration

Abstract: The extracellular milieu is comprised in part by products of cellular secretion and cell surface shedding. The presence of such molecules of the sheddome and secretome in the context of the extracellular milieu may have important clinical implications. In cancer they have been hypothesized to play a role in tumor growth and metastasis. The objective of this study was to evaluate whether the sheddome/secretome from two cell lines could be correlated with their potential for tumor development. Two epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
1
37
0
2
Order By: Relevance
“…( table 1 ). Considering the fold change of 1.5 [Aragão et al, 2012a;Paes Leme et al, 2012], amylase has similar abundance among the samples and it was identified in a notable manner with the highest spectral counts, which means a high abundance of this protein in the acquired enamel pellicle independently of the enamel pretreatment. This result is consistent with earlier findings that indicated that amylase is one of the major components of pellicle [Hannig et al, 2004[Hannig et al, , 2005Siqueira et al, 2012b].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…( table 1 ). Considering the fold change of 1.5 [Aragão et al, 2012a;Paes Leme et al, 2012], amylase has similar abundance among the samples and it was identified in a notable manner with the highest spectral counts, which means a high abundance of this protein in the acquired enamel pellicle independently of the enamel pretreatment. This result is consistent with earlier findings that indicated that amylase is one of the major components of pellicle [Hannig et al, 2004[Hannig et al, , 2005Siqueira et al, 2012b].…”
Section: Resultsmentioning
confidence: 94%
“…All datasets of proteins were processed using the workflow feature in Proteome Discoverer software v. 1.3 and the msf files were analyzed in ScaffoldQ+ v. 3.3.2 (Proteome Software), filtered using Xcorr cutoffs (+1 > 1.8, +2 > 2.2, +3 > 2.5 and +4 > 3.5), using the normalized number of total spectra counting to evaluate the protein abundance [Didangelos et al, 2011;Aragão et al, 2012a]. Spectral count normalizing entails averaging the spectrum counts across the samples, and then multiplying the spectrum counts in each sample by the average divided by the individual sample sum.…”
Section: Discussionmentioning
confidence: 99%
“…and searched against the NCBI Database (11346708 sequences; 3868708671 residues; Version 2011; Fungi Taxonomy:678749 sequences) using the MASCOT v.2.3.01 (Matrix Science Ltd.) search engine with carbamidomethylation as a fixed modification, oxidation of methionine as a variable modification, one trypsin missed cleavage and a tolerance of 0.1 Da for both precursors and fragment ions. Only peptides with a minimum of six amino acid residues that showed significant threshold (p<0.05) in Mascot-based score were considered in the results [26]. The false positive identification was minimized using a cutoff corresponding to a protein confidence level of 95% (FDR of <1.0%).…”
Section: Methodsmentioning
confidence: 99%
“…Defective expression of syndecan‐1 in mice results in defects in wound healing . The decrease of syndecan‐1 expression on tumor cells is associated with the release of the molecule from the cell surface as well as cytoplasmic or nuclear sequestration . Syndecan‐1 can be cleaved from the cell surface by the action of matrix metalloproteinases under the influence of chemokines .…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of syndecan‐1 is shown to be associated with the higher risk of metastasis and unfavorable outcome in head and neck SCC . The decrease of syndecan‐1 expression on tumor cells is shown to be associated with the release of the molecule from the cell surface as well as cytoplasmic or nuclear sequestration . In head and neck SCC, the decrease in the expression of the syndecan‐1 molecule is reported to be concomitant with the induction of its expression in the stromal cells of the tumor, which correlates with the recurrence and tumor‐specific death in 2 years follow‐up …”
Section: Introductionmentioning
confidence: 96%